2021
DOI: 10.7150/thno.58779
|View full text |Cite|
|
Sign up to set email alerts
|

Preventing tumor progression to the bone by induced tumor-suppressing MSCs

Abstract: Background: Advanced breast cancer metastasizes to many organs including bone, but few effective treatments are available. Here we report that induced tumor-suppressing (iTS) MSCs protected bone from metastases while un-induced MSCs did not. Methods: iTS MSCs were generated by overexpressing Lrp5, β-catenin, Snail, or Akt. Their tumor-suppressing capability was tested using a mouse model of mammary tumors and bone metastasis, human breast cancer tissues and cancer cell lines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(88 citation statements)
references
References 50 publications
(35 reference statements)
4
72
0
Order By: Relevance
“…We have shown that the overexpression of Lrp5, a Wnt co-receptor, stimulated the proliferation and migration of breast cancer cells 1 . To our surprise, however, we have also shown that the conditioned medium, collected from Lrp5-overexpressing osteocytes and MSCs, can suppress tumor growth 2 . Collectively, Wnt signaling presented a conflicting pair of actions as an intracellular tumor promoter in tumor cells and a generator of tumor-suppressing proteins in osteocytes and MSCs.…”
Section: Introductionmentioning
confidence: 85%
“…We have shown that the overexpression of Lrp5, a Wnt co-receptor, stimulated the proliferation and migration of breast cancer cells 1 . To our surprise, however, we have also shown that the conditioned medium, collected from Lrp5-overexpressing osteocytes and MSCs, can suppress tumor growth 2 . Collectively, Wnt signaling presented a conflicting pair of actions as an intracellular tumor promoter in tumor cells and a generator of tumor-suppressing proteins in osteocytes and MSCs.…”
Section: Introductionmentioning
confidence: 85%
“…While these agents significantly improve the quality of life in patients with bone metastasis and the risk of bone fracture, their efficacy is in many cases insufficient to prevent tumor-induced bone loss and eliminate cancer cells from the bone. To examine the possibility of developing a novel treatment option, we herein examined a recent technology of induced tumor-suppressing cells (iTSCs) that was successfully applied to osteocytes, mesenchymal stem cells (MSCs), and tumor cells [ 10 , 11 , 12 , 13 ]. In the iTSC technology, a dichotomous role of oncogenic signaling in tumor promotion as well as in tumor suppression is utilized.…”
Section: Introductionmentioning
confidence: 99%
“…While the activation of Wnt signaling is one valid strategy to generate iTSCs, we have shown that the overexpression of Akt in PI3K signaling and Snail in the induction of EMT also generated iTSCs from MSCs [ 12 ]. In this study, we employed seven pharmacological agents that were known to promote tumor progression, via activating Wnt with BML284 [ 14 ], PI3K/Akt with YS49 [ 15 ], Oct4 with OAC2 [ 16 ], PKA with CW008 [ 17 ], EGF with NSC228155 [ 18 ], JAK/STAT with RCGD423 [ 19 ], and phospholipase C with m-3M3FBS [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although breast cancer is peculiarly prone to bone metastasis, our understanding of the molecular mechanism of bone metastasis in breast cancer is still limited. Induced tumor-suppressing mesenchymal stem cells protect bones from metastasis in breast tumors [ 6 ] and the bone microenvironment and soluble factors participate in breast cancer bone metastasis. In this complex signaling network, interleukin is a key regulator, affecting the differentiation and function of osteocytes, as both cancer cells and osteocytes secrete interleukin and express the corresponding receptors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%